PENGARUH GREEN BRAND POSITIONING, ATTITUDE, DAN KNOWLEDGE TERHADAP GREEN PURCHASE INTENTION (Studi Kasus pada Konsumen di Work Coffee) - Nurhidayatul Haq, - (2020)
This study looks at the phenomenon on environmental issues that are now taking place. In an effort to care about the environment, a coffee shop in Bandung, Work Coffee strives to conduct its business by reducing the adverse risks to the environment. This research aims to look at the influence of green brand positioning, attitude, and knowledge on green product purchase intention in Work Coffee. The population of this study was a consumer of Work Coffee during the last year, using the technique of measuring the number of samples of slovin technique, obtained a sample number of 100 people. The sample techniques in this study used random sampling techniques. This research is included as quantitative research. The method of data collection used is a questionnaire using a differential semantic scale. The data analysis technique used is descriptive and verificative analysis. The results showed that green brand positioning variables (X₁) had a positive effect and significant on to green product purchase intention (Y) at Work Coffee. The attitude variable towards green brand (X₂) positively affects and significant on green product purchase intention (Y) in Work Coffee. The green brand knowledge variable (X₃) positively affects and significant on the green product purchase intention (Y) in Work Coffee. Based on the results of the data, it can be concluded that if the higher the free variable that is green brand positioning, attitude towards green brand, and green brand knowledge, then green product purchase intention consumers Work Coffee will also increase. Independent variables had an effect of 46.8%, of which 53.2% were influenced by other factors not studied. So it is suggested, for further research discussing other factors that can better describe the influence on green purchase intention.